The Effect Of Store Atmosphere And Service Quality On Impulse Buying At Alfamart Pasar Lama Lahat - Delviera Putri Kusuma; Nidyawati Nidyawati; Heri Fitriadi (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
The purpose of this study was to determine the effect of store atmosphere and service quality on impulse buying at Alfamart Pasar Lama Lahat. The results showed that (1) store atmosphere has a significant partial effect on impulse buying, as evidenced by the calculated t-value > t-table (7.089 > 1.993). (2) service quality has a significant partial effect on impulse buying, as evidenced by the calculated t-value > t-table (2.872 > 1.993). (3) store atmosphere and service quality have a significant simultaneous effect on impulse buying at Alfamart Pasar Lama Lahat, as evidenced by the calculated f-value > f-table (61.236 > 3.927), with a significance value lower than the significance level (a) of 0.05 (0.000 < 0.05).